2021
DOI: 10.47067/ramss.v4i4.182
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Critical Thinking Skills on Prospective Teachers’ Academic Achievement

Abstract: The study intention was to find the impact of critical thinking skills (CTS) on prospective teachers’ academic achievement. The method of the study was quantitative with correlation research design. The sample of the study was 113 prospective teachers using convenience sampling from three departments of teacher education institutions. To assess the Critical Thinking skills of prospective teachers, test was developed by the research comprised of five dimensions i.e. analyzing, assumption, deduction, inferences … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 14 publications
(15 reference statements)
1
2
0
Order By: Relevance
“…Besides, this study has shown that there was a positive and significant association amid QR achievement and CT skills amongst the study participants. This finding expressively concurred with the findings of some researchers (Okunuga, Awofala & Osarenren, 2020;Abbasi & Izadpanah, 2018;Ali & Awan, 2021;Kanbay, Işik, Aslan, Tektaş, & Kiliç, 2017;Kanwal, & Butt, 2021;Musa, 2020;Pozhhan, Goodarzi, & Roozbehani, 2019;Shirazi, & Heidari, 2019;Vierra, 2014;Ross, Leoffler, Schipper, Vandermeer, & Allan, 2013;Ghanizadeh, 2017;Jacob, 2012;Taghva, Rezaei, Ghaderi, & Taghva, 2014) that a significant relationship exists between critical thinking and educational performance. Nonetheless, this outcome disagreed with the results of others who had found no statistically momentous relationship between CT and educational outcome (Doleck, Bazalais, Lemay, Saxena, & Basnet, 2017;Bakhshi & Ahanchian, 2013).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Besides, this study has shown that there was a positive and significant association amid QR achievement and CT skills amongst the study participants. This finding expressively concurred with the findings of some researchers (Okunuga, Awofala & Osarenren, 2020;Abbasi & Izadpanah, 2018;Ali & Awan, 2021;Kanbay, Işik, Aslan, Tektaş, & Kiliç, 2017;Kanwal, & Butt, 2021;Musa, 2020;Pozhhan, Goodarzi, & Roozbehani, 2019;Shirazi, & Heidari, 2019;Vierra, 2014;Ross, Leoffler, Schipper, Vandermeer, & Allan, 2013;Ghanizadeh, 2017;Jacob, 2012;Taghva, Rezaei, Ghaderi, & Taghva, 2014) that a significant relationship exists between critical thinking and educational performance. Nonetheless, this outcome disagreed with the results of others who had found no statistically momentous relationship between CT and educational outcome (Doleck, Bazalais, Lemay, Saxena, & Basnet, 2017;Bakhshi & Ahanchian, 2013).…”
Section: Discussionsupporting
confidence: 90%
“…The existing works have exposed inconsistent outcomes regarding the relationship amid critical thinking and educational performance in which some researchers have revealed very robust association (Okunuga, Awofala & Osarenren, 2020;Ali & Awan, 2021;Kanbay, Işik, Aslan, Tektaş, & Kiliç, 2017;Kanwal, & Butt, 2021;Musa, 2020;Pozhhan, Goodarzi, & Roozbehani, 2019;Shirazi, & Heidari, 2019;Vierra, 2014;Ross, Leoffler, Schipper, Vandermeer, & Allan, 2013;Ghanizadeh, 2017) while other researchers have found no relationship (Doleck, Bazalais, Lemay, Saxena, & Basnet, 2017;Bakhshi & Ahanchian, 2013). In the context of Nigeria, there is a proof of little research done regarding the association amid scholastic performance and CT (Okunuga, Awofala & Osarenren, 2020;Chukwuyenum, 2013) notwithstanding the importance of CT in learners' performance in any course.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, critical thinking training can be started for prospective teachers, so in their professional career, they can train their students effectively. However, a recent study showed concern about the poor critical thinking performance of prospective science teachers [12]. For sustainable development, effective teaching innovations need to be implemented.…”
Section: Introductionmentioning
confidence: 99%